2016
DOI: 10.2147/jir.s110621
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of nonunions with application of BMP-7 increases the expression pattern for angiogenic and inflammable cytokines: a matched pair analysis

Abstract: The local application of bone morphogenetic protein-7 (BMP-7) in combination with the transplantation of autologous bone graft improves the outcome in nonunion treatment; however, the specific reasons remain unclear. In this study, we sought to determine if the local application of BMP-7 contributes to improved bone regeneration in nonunion therapy by modulation of the angiogenic and inflammable cytokine expression patterns of the early inflammation response. Therefore, we utilized the analysis of serological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 61 publications
3
27
0
Order By: Relevance
“…The inclusion and exclusion criteria were chosen to reduce possible confounders and to increase the consistency and thereby quality and reliability of our data and have been established in multiple previous studies [ 11 , 13 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The inclusion and exclusion criteria were chosen to reduce possible confounders and to increase the consistency and thereby quality and reliability of our data and have been established in multiple previous studies [ 11 , 13 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, CEUS has been shown to be effective in monitoring the vascularity of non-unions [ 9 ] and distinguishing preoperatively based on the microperfusion between infected and non-infected non-unions [ 9 ]. In addition, bone regeneration correlates with changes in the serum expression pattern of pro-angiogenic and pro-inflammatory cytokines [ 2 , 13 , 14 , 15 ]. Recently, the systemic analysis of markers associated with bone regeneration assessed by measurement of serum cytokine expression analysis (CEA) was established as a valid method in the timely evaluation of biological processes occurring during fracture healing and bone regeneration [ 2 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 While the gold standard intervention for these cases is the autologous bone graft, limited tissue available for harvest, the creation of a second surgical site, and donor site co-morbidity have necessitated the search for alternative therapeutic strategies. [5][6][7][8][9][10][11][12][13][14] One strategy that has become particularly prominent is the application of exogenous recombinant human bone morphogenetic protein 2 (rhBMP-2) via an absorbable collagen sponge (ACS). 15,16 This product currently has four United States Food and Drug Administration (FDA) approved clinical indications: spinal fusions, tibial shaft fractures, maxillary sinus lift, and alveolar ridge augmentations.…”
mentioning
confidence: 99%